Problems Experienced by Juvenile Care Center Inmates in the United Arab Emirates - BinSandal, Mira; AlHourani, Mohammed (Al-Adab Journal, 2025)
This study focuses on identifying and understanding the specific challenges faced by residents within juvenile care centers in the United Arab Emirates, shifting the emphasis from the broader issue of juvenile delinquency to the internal dynamics and experiences of these juveniles. Despite juvenile delinquency being a widespread phenomenon that poses a deviation from the norms and traditions of Emirati society, the core objective here is to dissect and analyze the problems encountered by juveniles residing in care centers, such as psychological distress, educational setbacks, and social integration issues. The research delves into the nature of the care environment, examining how it impacts the rehabilitation process and overall well-being of its residents. It aims to explore the living conditions, the provision of educational and vocational training, the psychological support available, and the strategies implemented to facilitate the reintegration of juveniles into society. The focus is squarely on evaluating the effectiveness of these juvenile care centers in addressing the needs of their residents and identifying areas where improvements are necessary. By concentrating on the internal challenges within these centers, the study seeks to contribute valuable insights into enhancing the care and support provided to juvenile residents. This approach not only aids in better understanding the immediate needs of these individuals but also offers a foundation for developing more effective rehabilitation programs. Through this focused examination, the study endeavors to present strategies that could significantly improve the quality of life for juveniles in care centers in the UAE, thereby aiding in their successful reintegration into society and enhancing social cohesion and moral conduct within the Emirati context.